Antiprotozoal Isoflavan Quinones from Abrus precatorius ssp. africanus - Hata, Yoshie; Raith, Melanie; Ebrahimi, Samad Nejad; Zimmermann, Stefanie; Mokoka, Tsholofelo; Naidoo, Dashnie; Fouche, Gerda; Maharaj, Vinesh; Kaiser, Marcel; Brun, Reto; Hamburger, Matthias (Planta Medica, 2013)
A library of 206 extracts from selected South African plants was screened in vitro against a panel of protozoan parasites, Plasmodium falciparum, Trypanosoma brucei rhodesiense, and Leishmania donovani. A CH2Cl2/MeOH (1 : 1) extract of Abrus precatorius L. ssp. africanus strongly inhibited P. falciparum (98 %), T. b. rhodesiense (100 %), and L. donovani (76 %) when tested at a concentration of 10.0 µg/mL. The active constituents were tracked by HPLC-based activity profiling and isolated by preparative and semipreparative RP-HPLC chromatography. Structures were established by HR-ESIMS, and 1D and 2D NMR (1H, 13C, COSY, HMBC, HSQC, and NOE difference spectroscopy). Five compounds were obtained and identified as two isoflavan hydroquinones, abruquinone H (1) and abruquinone G (2), and three isoflavan quinones, abruquinone I (3), abruquinone B (4), and 7,8,3′‚5′-tetramethoxyisoflavan-1′,4′-quinone (5). Compounds 1 and 3 were new natural products. The absolute configuration of compounds was determined by comparison of electronic circular dichroism spectra with calculated ECD data. Compounds 3 and 4 showed strong activity against T. b. rhodesiense (IC50 values of 0.30 and 0.16 µM, respectively) and good selectivity (selectivity indices of 73.7 and 50.5, respectively).
Keywords: antiprotozoal; Trypanosoma brucei rhodesiense; isoflavan quinone; Abrus precatorius; Fabaceae; electronic circular dichroism